Angiotensin converting enzyme inhibitors do not increase the risk of poor outcomes in COVID-19 disease. A multi-centre observational study. Issue 4 (November 2020) - Khan, Khurram Shahzad; Reed-Embleton, Hamish; Lewis, Jen; Bain, Pamela; Mahmud, Sajid
Background and aims: Hypertension is associated with an increased risk of severe outcomes with COVID-19 disease. Angiotensin Converting Enzyme (ACE) inhibitors are widely used as a first line medication for the treatment of hypertension in the UK, although their use was suggested in early reports to increase the risk associated with SARS-CoV-2 infection. Methods: A prospective cohort study of hospitalised patients with laboratory confirmed COVID-19 was conducted across three hospital sites with patients identified on the 9th April 2020. Demographic and other baseline data were extracted from electronic case records, and patients grouped depending on ACE inhibitor usage or not. The 60-day all-cause mortality and need for intubation compared. Results: Of the 173 patients identified, 88 (50.8%) had hypertension. Of these 27 (30.7%) used ACE inhibitors. We did not find significant differences in 60-day all-cause mortality, the requirement for invasive ventilation or length of stay between our patient cohorts after adjusting for covariates. Conclusion: This study contributes to the growing evidence supporting the continued use of ACE inhibitors in COVID-19 disease, although adequately powered randomised controlled trials will be needed to confirm effects.